Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1093/jnci/57.3.683
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chromosome Abnormality in Human Neuroblastoma and Antifolate-Resistant Chinese Hamster Cell Lines in Culture 1 2

Abstract: Four cell lines, SK-N-SH, SK-N-MC, SK-N-BE(2), and IMR-32, established in vitro from tumor tissue of patients with neuroblastoma were analyzed by trypsin-Giemsa banding methods. In two of the lines a large, abnormally staining chromosome region was observed. This "homogeneously staining region" (HSR) was considerably longer than any of the bands present in normal human cells and, as revealed by both G- and Q-banding, stained with an intermediate intensity. It was located on chromosomes No 6, 10, 17, or 19 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(126 citation statements)
references
References 0 publications
6
120
0
Order By: Relevance
“…Certain cell lines contain amplified sequences that appear to replicate synchronously with respect to one another and therefore behave as ifthey were composed of one or a few replicon types (1,2). These sequences are found in a variety of methotrexate (MTX)-resistant mouse and hamster cell lines, and arise through the amplification of a large segment which includes the gene for dihydrofolate reductase (DHFR; tetrahydrofolate dehydrogenase; 5,6,7,8-tetrahydrofolate:NADP' oxidoreductase, EC 1.5.1.3) (3-6) as well as unknown other genetic material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Certain cell lines contain amplified sequences that appear to replicate synchronously with respect to one another and therefore behave as ifthey were composed of one or a few replicon types (1,2). These sequences are found in a variety of methotrexate (MTX)-resistant mouse and hamster cell lines, and arise through the amplification of a large segment which includes the gene for dihydrofolate reductase (DHFR; tetrahydrofolate dehydrogenase; 5,6,7,8-tetrahydrofolate:NADP' oxidoreductase, EC 1.5.1.3) (3-6) as well as unknown other genetic material.…”
mentioning
confidence: 99%
“…These sequences are found in a variety of methotrexate (MTX)-resistant mouse and hamster cell lines, and arise through the amplification of a large segment which includes the gene for dihydrofolate reductase (DHFR; tetrahydrofolate dehydrogenase; 5,6,7,8-tetrahydrofolate:NADP' oxidoreductase, EC 1.5.1.3) (3-6) as well as unknown other genetic material. Several hundred copies of the amplified sequence are arranged in tandem on one or a few chromosome arms, and constitute homogeneously staining regions (HSRs) on mitotic chromosomes when subjected to G-and C-banding protocols (1,3,4,6). It has been shown that the HSRs in Chinese hamster lines begin to synthesize DNA over their length synchronously at many loci at the very beginning ofthe S period; in one ofthese lines, replication of the HSR is completed by the third hour of a 7-hr S period (2).…”
mentioning
confidence: 99%
“…* P < 0.05 relative to untreated control. [18][19][20]. YS71 and YS80 displayed similar efficacy in the resistant neuroblastoma cell lines compared to UKF-NB-3 as indicated by fold changes IC 50 resistant cell line/ IC 50 UKF-NB-3 < 2.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, we determined the effects of these compounds on the viability of Be(2)-C cells. Be(2)-C is a clonal subline of the neuroblastoma cell line SK-N-BE(2) that was isolated from a neuroblastoma patient after repeated courses of chemotherapy and radiotherapy [18] and that displays multi-drug resistance [19,20].…”
Section: Effects Of Selected Pirinixic Acid Derivatives On the Viabilmentioning
confidence: 99%
“…Homogeneously staining regions (HSR) are novel chromosome abnormalities which stain uniformly instead of the pattern of alternating pale and dark bands seen in normal chromosomes when stained with either trypsin-Giemsa or other banding procedures (Biedler and Spengler, 1976). Double minute chromosomes (drain), another type of unusual abnormality (Spriggs et al, 1962), are small, paired chromatin bodies whose number and size vary from one cell to another (Barker and Hsu, 1979;Cox et al, 1965).…”
Section: Introductionmentioning
confidence: 99%